Strong T-cell activation in response to COVID-19 vaccination in multiple sclerosis patients receiving B-cell depleting therapies - Alfonso-Dunn, Roberto; Lin, Jerry; Kirschner, Vanessa; Lei, Joyce; Feuer, Grant; Malin, Michaela; Liu, Jiayuan; Roche, Morgan; Sadiq, Saud A. (Frontiers in Immunology, 2022)
Immunocompromised individuals, including multiple sclerosis (MS) patients under certain immunotherapy treatments, are considered susceptible to complications from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and specific vaccination regimens have been recommended for suitable protection. MS patients receiving anti-CD20 therapy (aCD20-MS) are considered especially vulnerable due to acquired B-cell depletion and impaired antibody production in response to virus infection and COVID-19 vaccination. Here, we report a strong polyfunctional T-cell response in aCD20-MS patients during the first 6 months after a 2-dose cycle mRNA-based vaccination. This response is significantly higher than the one observed from a healthy control group, even under conditions of severe B-cell depletion and failed seroconversion. Moreover, no difference in T-cell response was observed between forms of disease, anti-CD20 therapy and type of mRNA-based vaccine received. These results suggest the generation of a partial adaptive immune response to COVID-19 vaccination in B-cell depleted individuals driven by a functionally competent T-cell arm. Investigation into the role of the cellular immune response is important to identifying the level of protection against SARS-CoV-2 in aCD20-MS patients, and could have potential implications for future vaccine design and application.